Preparation of copper doped zinc oxide nanoparticles by precipitation process for humidity sensing device - Thutiyaporn Thiwawong; Korakot Onlaor; Natpasit Chaithanatkun; Benchapol Tunhoo (My University, 2018)
In this work, nanoparticles of copper-doped zinc oxide were synthesized using the precipitation process at different copper doping molars. The structure of the synthesized nanoparticles was examined by X-ray diffraction and X-ray photoelectron spectroscopy. From the results, it was indicated that the nanoparticles were composed of mixed copper oxide-zinc oxide. To fabricate the humidity sensor, the nanoparticles were dispersed in ethanol and deposited on an electrode using the electrostatic spray deposition technique. The humidity sensing behavior was assessed at various humidity levels in a closed vessel of saturated salt solution. Moreover, the response times for the device were recorded. The Cole-Cole plot of the real and imaginary parts of impedance could be useful for description of the equivalent circuit that indicates the mechanism for humidity sensing behavior.
Keywords: Copper oxide; Gas Sensing Nanomaterials and Sensors